Analysis of site and structure specific core fucosylation in liver cirrhosis using exoglycosidase-assisted data-independent LC-MS/MS - Sanda, Miloslav; Ahn, Jaeil; Kozlik, Petr; Goldman, Radoslav (Scientific reports, 2021)
Carbohydrates form one of the major groups of biological macromolecules in living organisms. Many biological processes including protein folding, stability, immune response, and receptor activation are regulated by glycosylation. Fucosylation of proteins regulates such processes and is associated with various diseases including autoimmunity and cancer. Mass spectrometry efficiently identifies structures of fucosylated glycans or sites of core fucosylated N-glycopeptides but quantification of the glycopeptides remains less explored. We performed experiments that facilitate quantitative analysis of the core fucosylation of proteins with partial structural resolution of the glycans and we present results of the mass spectrometric SWATH-type DIA analysis of relative abundances of the core fucosylated glycoforms of 45 glycopeptides to their nonfucosylated glycoforms derived from 18 serum proteins in liver disease of different etiologies. Our results show that a combination of soft fragmentation with exoglycosidases is efficient at the assignment and quantification of the core fucosylated N-glycoforms at specific sites of protein attachment. In addition, our results show that disease-associated changes in core fucosylation are peptide-dependent and further differ by branching of the core fucosylated glycans. Further studies are needed to verify whether tri- and tetra-antennary core fucosylated glycopeptides could be used as markers of liver disease progression.
Keywords: Glycopeptides; Glycoside Hydrolases; Chromatography, Liquid; Humans; Tandem Mass Spectrometry; jaterní cirhóza; lidé; Biomarkers; Liver Cirrhosis; fukosa; Fucose; tandemová hmotnostní spektrometrie; glykosidhydrolasy; biologické markery; chromatografie kapalinová; glykosylace; Polysaccharides; polysacharidy; Glycosylation; glykopeptidy